PENGARUH SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTEREN TERHADAP PENERIMAAN OPINI WTP PADA PEMERINTAH DAERAH KABUPATEN TANAH DATAR - Amran, Elsa Fitri; Saputri, Ramadhani; Guspendri, Nasfizar; Fitri, Sri Adella; Nofrivul, Nofrivul (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the effect of accounting information systems and internal control systems on the acceptance of WTP opinions in the Regional Government of Tanah Datar Regency. This type of research is a type of field research (Field Research) with a quantitative approach. The technique used in sampling is Quota Sampling. Data analysis techniques used were validity, reliability, descriptive statistical analysis, and classical assumption tests, multiple linear analysis tests, and hypothesis testing, with the help of the SPSS version 26 program. The results showed that the application of accounting information systems had a significant effect on acceptance of WTP Opinion Tanah Datar District Government. The internal control system has no significant effect on the acceptance of WTP opinion at the Regional Government of Tanah Datar Regency. The accounting information system and internal control system have a significant effect on the acceptance of WTP opinions in the Regional Government of Tanah Datar Regency. The accounting information system and internal control system have a significant effect on the acceptance of WTP opinion at the Tanah Datar District Government together. Keywords: Accounting Information System; Internal Control System; and Opinion of WTP